State of the art – Extracorporeal membrane oxygenation as a bridge to thoracic transplantation. Issue 2 (18th December 2022) - Orozco‐Hernandez, Erik; DeLay, Thomas Kurt; Gongora, Enrique; Bellot, Chris; Rusanov, Victoria; Wille, Keith; Tallaj, Jose; Pamboukian, Salpy; Kaleekal, Thomas; Mcelwee, Sam; Hoopes, Charles
Abstract: Background: Extracorporeal membrane oxygenation (ECMO) has revolutionized the treatment of refractory cardiac and respiratory failure, and its use continues to increase, particularly in adults. However, ECMO‐related morbidity and mortality remain high. Main Text: In this review, we investigate and expand upon the current state of the art in thoracic transplant and extracorporeal life support (ELS). In particular, we examine recent increase in incidence of heart transplant in patients supported by ECMO; the potential changes in patient care and selection for transplant in the years prior to updated United Network for Organ Sharing (UNOS) organ allocation guidelines versus those in the years following, particularly where these guidelines pertain to ECMO; and the newly revived practice of heart‐lung block transplants (HLT) and the prevalence and utility of ECMO support in patients listed for HLT. Conclusions: Our findings highlight encouraging outcomes in patients bridged to transplant with ECMO, considerable changes in treatment surrounding the updated UNOS guidelines, and complex, diverse outcomes among different centers in their care for increasingly ill patients listed for thoracic transplant.